Rural development in India : current perspectives - Mohinder Singh, ed. (New Delhi, 1992)
Rural development has emerged as a major strategy of the developmental proc ess of India to achieve multiple objectives, viz., higher rate of production, generation. of more employment, reduction in inequali ties of incomes and assets, establishment of participatory development, enhanced ac cess to modern inputs and extension serv ices, greater self-reliance and creation of environmental awareness among the rural masses. Since 50s, a number of program mes of rural development are in operation and in particular, programmes like the CDP, PRI, IRDP, NREP, etc., have been implemented vigorously, as a result of which rural development has acquired spe cial significance in the developmental proc ess of our country. The book in hands com prises papers contributed by experienced academicians, researchers and administra tors from different disciplines. It is devoted to evaluating the impact of important pro grammes of rural development, critical ex amination thereof and suggesting appropri ate measures for bettering them. Broadly, this book presents current perspectives on IRDP, Panchayati Raj, People's Participa tion, Land Distribution, Irrigation, Health Services, Industrialisation, Interlocked Fac tor Markets, Poverty, Measuring Rural De velopment, Voluntary Agencies and New Scientific Approach to Rural Transforma tion.
Keywords: Rural development India